THE INFLUENCE OF INCOME LEVEL ON CLASSROOM MANAGEMENT COMPETENCY OF ISLAMIC RELIGIOUS TEACHERS AT MTs IN TATANGA DISTRICT - Safira Arifa Safira; Rustina; Wiwin Mistiani (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of income level on classroom management competency of Islamic Religious Education teachers at MTs in Tatanga District. The study employed a correlational quantitative approach with an associative causal ex post facto design. The entire population of 32 Islamic Religious Education teachers was used as the sample through a saturated sampling technique. Data were collected through a Likert Scale-based questionnaire, documentation, and non-participant observation, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results of the measurement model testing indicate that all indicators met the validity and reliability criteria with outer loading values ranging from 0.771 to 0.931. The structural model testing proves that income level has a positive and significant influence on classroom management competency with a path coefficient value of 0.985 and an R-Square of 0.970. This means that 97.0% of the variation in classroom management competency can be explained by teachers' income level. These findings affirm that teachers' financial well-being is a structural factor that greatly determines the quality of classroom management, while simultaneously serving as a strategic policy basis in efforts to achieve SDGs Goal 4 on quality education.